Pengaruh Corporate Social Responsibility (CSR) Dan Return On Asset (ROA) Pada Good Corporate Governance (GCG) (Akmenika, 2016)
This study aimed to examine the influence of social responsibility (Corporate SocialResponssibility) and profitability (return on assets) on corporate governance (GCG).This study was performed on companies listed in the Stock Exchange in 2011-2013.Sampling method with purposive sampling and data collection methods withobservation. This study tested with multiple regression analysis to test the hypothesis ttest with significance of 5%.Hypothesis testing results show there is influence of CSR(Corporate Social Responsibility) in GCG with t test of 4.486 with 0.000 significanceand ROA affect the GCG with t value of 2.160 with 0.036 significance. These resultsindicate that the hypothesis 1 and 2 are supported. The higher CSR undertaken by thecompany the higher the GCG companies, as well as higher profitability (ROA), thehigher the GCG. Based on F test of 11.72 with a significance of 0,000 showed jointlybetween CSR and corporate governance affect the ROA. This suggests the hypothesis 3is supported. which means jointly CSR and ROA effect on corporate governance. If CSRrose by 1 then GCG will rise 0054, as well as ROA rose by 1 it will increase the GCG of0.015. Adjusted R2 value of 0.195 which demonstrates the ability of CSR (CorporateSocial Responsibility) and profitability (ROA) can explain GCG amounted to 19.50%,while the remaining 80.50% is explained by other variables